Transcription pausing regulates mouse embryonic stem cell differentiation - Melodi Tastemel; Aishwarya A. Gogate; Venkat S. Malladi; Kim Nguyen; Courtney Mitchell; Laura A. Banaszynski; Xiaoying Bai (Stem Cell Research, 2017)
The pluripotency of embryonic stem cells (ESCs) relies on appropriate responsiveness to developmental cues. Promoter-proximal pausing of RNA polymerase II (Pol II) has been suggested to play a role in keeping genes poised for future activation. To identify the role of Pol II pausing in regulating ESC pluripotency, we have generated mouse ESCs carrying a mutation in the pause-inducing factor SPT5. Genomic studies reveal genome-wide reduction of paused Pol II caused by mutant SPT5 and further identify a tight correlation between pausing-mediated transcription effect and local chromatin environment. Functionally, this pausing-deficient SPT5 disrupts ESC differentiation upon removal of self-renewal signals. Thus, our study uncovers an important role of Pol II pausing in regulating ESC differentiation and suggests a model that Pol II pausing coordinates with epigenetic modification to influence transcription during mESC differentiation.